Rapunzel Syndrome: A Case of Trichobezoar with Small Bowel Complications - Narra, Ramakrishna; Guntamukkala, Anusha; Rao, Chanda Bhaskara; Begum, Tanveer (The Surgery Journal, 2022)
Introduction Rapunzel syndrome is characterized by a large trichobezoar in the stomach with a tail extending beyond the pylorus into the small bowel, causing mechanical obstruction of the small bowel. A 7-year-old girl presented to the emergency room with severe epigastric pain. Computed tomography suggested trichobezoar causing jejuno-jejunal intussusceptions, bowel wall thickening, and dilated small bowel loops proximal to the obstruction. On laparotomy, two concealed perforations were noted at the duodenojejunal (DJ) junction and 40 cm distal to the DJ junction. An enterotomy incision was given at the antimesenteric border of the distal jejunal perforation site, and the mass was successfully extracted. Primary repair was done at the DJ perforation site, and resection was followed by an end-to-end anastomosis at the distal jejunal perforation site. Surgery confirmed a complex mass of tangled hair within the gastric cavity with a tail extending into the pylorus of the stomach and small intestine, consistent with trichobezoar.Conclusion Computed tomography is superior to other radiological imaging modalities for diagnosing trichobezoars as it helps diagnose and demonstrate mechanical bowel complications.
Keywords: trichobezoar; Rapunzel syndrome; intussusceptions; contrast-enhanced computed tomography